Direct foreign investment and Nigeria's balance of payments - Agba, A. V. (Ibadan : Evi-Coleman Publications, 2002)
Examines how Foreign Direct Investment (FDI) in Nigeria has impacted in the country's balance of payment and the economy.
Includes index.
Includes bibliographical references (p. 248-262).
oif 26/07/2015
Loan
Keywords: Balance of payments; Investments, Foreign; Economic policy; Economic conditions; Nigeria